Analisis Standarisasi Motu Produk Halal Dan Hki Bagi Usaha Mikro Kecil Menengah Air Sebakul Bengkulu Tengah - Valentino, Aldi Valentino (Universitas Dehasen Bengkulu, 2023)
Entering the Industrial 4.0 era, Indonesia must immediately adjust its position so that it can become a production base and logistics center by taking advantage of opportunities to expand market share, while at the same time being able to integrate itself into the global supply chain. One of the strategies to integrate this is to make Halal Product Micro, Small and Medium Enterprises (MSMEs) the subject of the national strategy in an effort to encourage the development of national geopolitical and geoeconomic potential. As the main subject of this strategy, problems for MSME actors are still a fundamental problem in Indonesia. The ineffectiveness of capital distributed by the government and the complexity of the bureaucratic system resulted in slow growth of MSMEs, resulting in a gap between the behavior of MSMEs and the government. The government in this case seems serious about encouraging domestic industry players to improve the quality of halal products so they can compete in the industrial era 4.0. In an effort to stabilize the economy, the government began to distribute budgets to industry players, especially MSMEs in Indonesia. Deputy for Financing of the Ministry of Cooperatives and SMEs (Kemkop UKM) Yuana Styawati said the number of micro businesses until 2018 was 58.91 million units, 59,260 small businesses and 4,987 large businesses. In addition, it was also recorded that 3.79 million MSMEs had utilized digital technology or e-commerce businesses (Maizal Walfajri, 2018). Of this amount, the government distributes a budget for small and medium enterprises in the amount of Rp. 1.2 trillion, of which this amount will be distributed using two schemes, namely distribution with conventional schemes and sharia schemes as well as assistance or facilitation efforts for the MSME industry in Halal Products.The existence of Small and Medium Enterprises (SMEs) as creative businesses in Bengkulu is quite large, but there are still many people who do not understand the importance of Intellectual Property Rights for Micro, Small and Medium Enterprises. The problem we face from our socialization is how to raise awareness in the community that Intellectual Property Rights are very important for a creative business. The purpose of our socialization is to inform micro, small and medium entrepreneurs in Timur Indah 5 RT 32 RW 02 that Intellectual Property Rights play a very important role in protecting intellectual property rights owned by a Micro, Small and Medium Enterprises actor. This community service method uses the socialization method by approaching the community and providing knowledge about the importance of Intellectual Property Rights for Micro, Small and Medium Enterprises